Safety baseballs and chest protectors: A systematic review on the prevention of commotio cordis - Classie, J. A.; Distel, L. M.; Borchers, J. R. (The Physician and Sportsmedicine, 2010)
Objective To determine whether chest protectors and/or safety baseballs reduce the incidence of commotio cordis during sport through a review of the best available evidence Data sources PubMed, Ovid Medline, and Embase databases from 1950 to 2009. We selected articles according to "death, sudden, cardiac," "commotio cordis," "sports equipment," and "protective devices." We identified 17 articles in the systematic literature search. Of these, 7 articles met inclusion criteria. Three independent reviewers reviewed the articles. The study results and generated conclusions were extracted and agreed on. Results The softest safety baseball shows statistically significant reductions in the incidence of ventricular fibrillation (VF) at all velocities compared with standard baseballs in the 3 studies that evaluated their use. Different degrees of softness did not show statistically significant reductions in VF. In the 3 studies that evaluated the use of chest protectors against controls, there was an increase in protection against fatal arrhythmias; however, this was only statistically significant for 1 chest protector. Conclusions This systematic review shows strong supportive evidence toward a decreased rate of commotio cordis with safety baseballs when compared with standard balls. Based on the results of our systematic review, the rate of induction of VF was at its lowest when chest protection was used.